My Apple watch - Johnston, Craig James, 1967- (Que, 2016)
Step-by-step instructions with callouts to Apple Watch screenshots that show you exactly what to do. Help when you run into problems or limitations. Tips and Notes to help you get the most from your Apple Watch. Full-color, step-by-step tasks walk you through everything you want to do with your Apple Watch. Learn how to Create new watch faces and customize existing ones Customize what apps appear in Glances, what notifications you receive, and how your Apple Watch interacts with your iPhone Set up and use Apple Pay Use Siri to take actions on your behalf Quickly communicate with your friends Send Digital Touch sketches, taps, or your own heartbeat Install and manage Apple Watch apps Connect your Apple Watch to a Bluetooth headset or speaker Play music from your Apple Watch, or just control the music on your iPhone Control your iPhone's camera from your Apple Watch Keep track of your workouts, exercise, and calorie usage.